2016
DOI: 10.18203/2320-6012.ijrms20163322
|View full text |Cite
|
Sign up to set email alerts
|

Role of glycated hemoglobin (HBA1c) as a dual marker to predict glycemic status and dyslipidemia in type II diabetes mellitus

Abstract: INTRODUCTIONDiabetes is a global endemic with rapidly increasing prevalence in both developed and developing countries. 1 DM is a group of metabolic disease characterized by hyperglycemia resulting from defects in insulin secretion, insulin action or both. Uncontrolled diabetic patients are characterized by hyperglycemia, hyper insulinemia, protein glycation and oxidative stress which cause early appearance of diabetic complications.The chronic hyperglycemia is associated with long-term damage dysfunction, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…[30][31][32] HbA1c also demonstrated direct and significant correlations with cholesterol (r=0.6445), TGL (r= 0.5426), LDL-C(r=0.3584), VLDL (r=0.2245) -a strong positive correlation; whereas HDL-C showed negative correlation (r=-0.4965). 9 Jayesh et al conducted a prospective study on western Indian population that comprised of 430 T2DM patients and 501 non-diabetic control subjects. 33 Sultania et al found significant correlation of HbA1c with TC and LDL.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[30][31][32] HbA1c also demonstrated direct and significant correlations with cholesterol (r=0.6445), TGL (r= 0.5426), LDL-C(r=0.3584), VLDL (r=0.2245) -a strong positive correlation; whereas HDL-C showed negative correlation (r=-0.4965). 9 Jayesh et al conducted a prospective study on western Indian population that comprised of 430 T2DM patients and 501 non-diabetic control subjects. 33 Sultania et al found significant correlation of HbA1c with TC and LDL.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Diabetes mellitus (DM) is a common secondary cause of hyperlipidemia, particularly, if glycaemic control is poor. 9 Based on the American diabetic association (ADA) abnormal lipid profiles are when total cholesterol level ≥200 mg/dl, triglyceride level is ≥150 mg/dl, HDL level is <40 mg/dl in males and <50 mg/dl in females, LDL level is ≥100 mg/dl. Hence dyslipidemia was defined as the presence of one or more of the above-mentioned abnormalities in serum lipids.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increase in the serum levels of the hepatic enzymes may lead to reduced concentrations of total protein (TP) and albumin in the serum [7]. Poor glycaemic control during diabetes mellitus causes hyperlipidaemia, which is associated with an increased flux of free fatty acid due to insulin resistance [8,9].…”
Section: Introductionmentioning
confidence: 99%